The Problems of Personnel Training for STEM Education in the Modern Innovative Learning and Research Environment (Pedagogy of Higher and Secondary Education, 2018)
Shyshkina M.P. The Problems of Personnel Training for STEM Education in the Modern Innovative Learning and Research Environment.The aim of the article is to describe the problems of personnel training that arise in view of extension of the STEM approach to education, development of innovative technologies, in particular, virtualization,augmented reality, the use of ICT outsourcing in educational systems design. The object of research is the process of formation and development of the educational and scientific environment of educational institution. The subject of the study is the formation and development of the cloud-based learning and research environment for STEM education. The methods of research are: the analysis of publications on the problem; generalization of domestic and foreign experience; theoretical analysis, system analysis, systematization and generalization of research facts and laws for the development and design of themodel of the cloud-based learning environment, substantiation of the main conclusions. The results of the research are the next: the concepts and the model of the cloud-based environment of STEM education is substantiated, the problems of personnel training at the present stage are outlined.
Keywords: learning environment; cloud technologies; augmented realitу; pedagogical personnel